PEMBERDAYAAN KTT ARSE UNTUK PENINGKATAN USAHA KELOMPOK MELALUI IPTEK TELUR ASIN BERBASIS EKSTRAK BUAH ANDALIMAN (Zanthoxylum acanthopodium) DAN KECOMBRANG (Eltingera elatior) - Nasution, Zakiyah; Silaban, Rikardo; Harahap, Aris Munandar; Pane, Doharni; Nababan, Hotli H. (JURNAL ABDIMAS DOSMA (JAD), 2023)
Livestock sector is inseparable from the process of downstreaming animal raw product become the functional product or industrial needs (such as the processing of cosmetics based on dairy sources). One of the objectives of processing raw materials for livestock products is to increase efficiency and product quality as the functional food. The strategy that can be used to increase the productivity of livestock farmer groups (LFG) is to support programs that are carried out through the utilization of SAINTECH. This will also encourage the economic growth of the group members inline with improving their standard of living. The group focuses for implementation of functional food SAINTECH is a group of livestock farmers who are located among the Arse District, South Tapanuli Regency. The ultimate goal of this service is that the Arse LFG can process salted eggs based on typical spice plant extracts as functional dairy food, able to carry out the marketing system, and will increase thes incomes after using the SAINTECH product. The devotion applied the Consuling method (approaching, outreachment, and mentoring stages), monitoring and evaluating the results. Results describe that the interest of members in utilizing SAINTECH is approximately 82.17% (VERY GOOD), overall consumers are 3.40 (very receptive to the product) and income has increased based on business analysis. Therefore, it was concluded that the assistance of the Arse LFG through the application of SAINTECH in animal food processing showed an increase in quality based on observational indicators.